(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The results of these research shown the relation between Social growth of child and his studding achievement depending on how much family, school, and mate group influences on his Social growth positive, or negative, and on his studding achievement, there are static differences between Social ripeness and students studding achievement and it confirm that the child who has ripe Social growth, he well has a height degree in studding subjects, so he has good studding achievement. it confirms about the importance of mate group, and family, school for the child, where indicate to the educational importance role, which mate group, and family, school play in the children adaptation, and Social, intellectual, and emotional habilitation.